Protein Phosphatase 1 Regulates Human Cytomegalovirus Protein Translation by Restraining AMPK Signaling - Stecher, Carmen; Marinkov, Sanja; Mayr-Harting, Lucia; Katic, Ana; Kastner, Marie-Theres; Rieder-Rommer, Franz J. J.; Lin, Xionghao; Nekhai, Sergei; Steininger, Christoph (Frontiers in Microbiology, 2021)
Human cytomegalovirus (HCMV) carries the human protein phosphatase 1 (PP1) and other human proteins important for protein translation in its tegument layer for a rapid supply upon infection. However, the biological relevance behind PP1 incorporation and its role during infection is unclear. Additionally, PP1 is a difficult molecular target due to its promiscuity and similarities between the catalytic domain of multiple phosphatases. In this study, we circumvented these shortcomings by using 1E7-03, a small molecule protein-protein interaction inhibitor, as a molecular tool of noncatalytic PP1 inhibition. 1E7-03 treatment of human fibroblasts severely impaired HCMV replication and viral protein translation. More specifically, PP1 inhibition led to the deregulation of metabolic signaling pathways starting at very early time points post infection. This effect was at least partly mediated by the prevention of AMP-activated protein kinase (AMPK) dephosphorylation, leading to elongation factor 2 (EEF2) hyperphosphorylation and reduced translation rates. These findings reveal an important mechanism of PP1 for lytic HCMV infection.